Correction: Synthesis of flexible nanotweezers with various metals and their application in carbon nanotube extraction. (30th April 2018) - Miyake, Yuya; López-Moreno, Alejandro; Yang, Jian; Xu, Hai-Jun; Desbois, Nicolas; Gros, Claude P.; Komatsu, Naoki
Abstract : Correction for 'Synthesis of flexible nanotweezers with various metals and their application in carbon nanotube extraction' by Yuya Miyake et al., New J. Chem., 2018, DOI: ;10.1039/c8nj00147b .